2013
DOI: 10.1590/s0100-72032013000700008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor estromal esclerosante de ovário associado à síndrome de Meigs e gestação: relato de caso

Abstract: The sclerosing stromal tumor of the ovary is an extremely rare benign tumor more common in young women and without specific symptoms in most cases. Less than 150 cases have been described, of which 8 were diagnosed during pregnancy. In this report, we describe the association between sclerosing stromal tumor of the ovary, Meigs' syndrome and elevated levels of CA-125 in term pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Despite of imaging tests are capable of accenting peculiar characteristics of Ovarian Stromal Tumor, there is no pathognomonic finding. 2,5 The Preoperative preparation of the patient is routine, apart from in patients with virilization or signs of excess estrogen, in which the evaluation of tumor markers and the performance of an endometrial sample to detect a possible endometrial neoplasia may be indicated. 3 In the present case, due to the absence of signs that suggested malignancy, preoperative tumor markers or specific hormone levels were not requested because of the absence of signs of virilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite of imaging tests are capable of accenting peculiar characteristics of Ovarian Stromal Tumor, there is no pathognomonic finding. 2,5 The Preoperative preparation of the patient is routine, apart from in patients with virilization or signs of excess estrogen, in which the evaluation of tumor markers and the performance of an endometrial sample to detect a possible endometrial neoplasia may be indicated. 3 In the present case, due to the absence of signs that suggested malignancy, preoperative tumor markers or specific hormone levels were not requested because of the absence of signs of virilization.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 It is important to point out that chemotherapy is generally indicated for patients with advanced disease or recurrent thereby there is no scientific data that corroborates the effectiveness of this approach in patients with Granular Cell Tumors. 4 Another point that stands out is the issue of hormone therapy, which is not very widespread, but which presents promising results in patients with severe or recurrent disease, since the hormonal blockade aims to reduce or extinguish cell Sclerosing stromal tumor of the ovary: case report Volume 14 Issue 4 -2023 Maria Luísa Buzatto, 1 Hellen Cruz Xavier, 1 Beatriz Guedes Fernandez, 1 Pedro Henrique Bertoleti Ribeiro, 1 Samuel Rabello, 2 Regis Vilela Leal, 3 Ana Clara de Moura Silva, 4 Fabiana Shimabuko da Silveira, 5 Tane Machado Scaloppe proliferation. 4 Finally, especially in less advanced stages, the surgical approach is the most indicated.…”
Section: Introductionmentioning
confidence: 99%